Starzenie sie populacji krajów Unii Europejskiej – nieodległa przeszłość i prognoza - Kowaleski, Jerzy T.; Majdzińska, Anna (Studia Demograficzne, 2012)
The aim of this paper is to describe population ageing in member countries of the European Union and its dynamics in the period 1990–2030. Furthermore, we show chosen social consequences and challenges caused by demographic ageing. In the introduction, we present definition of the population ageing and describe measures used in the paper. The analytical part consists of three sections. The first one is about growth of older population (at the age of 65 and over, and 80 and over) in the years 1990–2030. The next one comprises an evaluation of progress in demographic change in the EU countries, which is based on chosen measures of population structure – aging index (population 65 and over to population 0–14), and potential support ratio (population 15–64 years to population 65 and over). In the analysis, we use also positional measures. The last part focuses on explaining regional differences in progress of demographic ageing of particular countries. The last section of the paper focuses on chosen socioeconomic consequences of ageing in the EU countries. One of them is an expected increase in number of disabled people. Another one is growth in the number of single person households of the elderly, who need familial and extra-familial care.